2011
DOI: 10.1117/12.882726
|View full text |Cite
|
Sign up to set email alerts
|

Robust discrimination of human footsteps using seismic signals

Abstract: This paper provides a statistical analysis method for detecting and discriminating different seismic activity sources such as humans, animals, and vehicles using their seismic signals. A five-step process is employed for this purpose: (1) a set of signals with known seismic activities are utilized to verify the algorithms; (2) for each data file, the vibration signal is segmented by a sliding-window and its noise is reduced; (3) a set of features is extracted from each window of the signal which captures its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In preparing class signatures, initially we tried to fuzzy classify all detected signals, however we were not able to map input signals to fuzzy input and output variables as in [75]. Thereafter, we have made use of acoustic and seismic data properties for the initial level classification as described in [76] and [77], respectively. For the acoustic detection, acoustic signal is analyzed to determine the presence of a target by using Binary Fuzzy Classification (BFC) as described in [78].…”
Section: Hierarchical Data Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preparing class signatures, initially we tried to fuzzy classify all detected signals, however we were not able to map input signals to fuzzy input and output variables as in [75]. Thereafter, we have made use of acoustic and seismic data properties for the initial level classification as described in [76] and [77], respectively. For the acoustic detection, acoustic signal is analyzed to determine the presence of a target by using Binary Fuzzy Classification (BFC) as described in [78].…”
Section: Hierarchical Data Fusionmentioning
confidence: 99%
“…For the seismic detection, initially detected signal is segmented into 0.75 second windows and for each window a set of features which forms the feature-vector are extracted. A total number of 60 features are defined by using spectral technique (Fourier transform), statistical techniques (mean and variance) and entropy of the signal as described in [77]. If the initial level classification result is human/vehicle, then a trigger is sent to the camera sensor on the node to activate it; if not we simply discard the result.…”
Section: Hierarchical Data Fusionmentioning
confidence: 99%
“…Sensor networks are common to use for human/animal classification [2], human footstep discrimination [3], condition monitoring in the railway industry [4], vehicle detection and classification [5,6], urban traffic management [7], vehicle speed estimation [8], supporting environments for multimedia surveillance [9], or discriminating humans, animals, and vehicles [10]. Tracked and trackless vehicle detection and classification with distributed sensor networks as a counter camouflage technique is also one of the popular application areas [11].…”
Section: Introductionmentioning
confidence: 99%
“…He [7] proposed a novel vibration-based fault diagnosis algorithm for a machine condition monitoring system using the wavelet packet transform (WPT) features. In addition to these studies, fruitful achievements on vibration processing can be found in [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%